Predictors of in-hospital death in children with myocardial injury related to COVID-19 - Souza Filho, César Augusto de Oliveira; Lima Junior, Emilton (The Journal of Infection in Developing Countries, 2024)
Introduction: Myocardial injury due to COVID-19 infection is associated with higher mortality rates, higher intensive care unit admissions, and greater levels of inflammatory and cardiac markers. However, given the smaller number of papers regarding pediatric patients, there is still scarce data about mortality predictors in this population. This study aims to identify independent predictors of in-hospital death among pediatric patients hospitalized with myocardial injury related to COVID‐19. Methodology: This is an observational, prospective, and longitudinal study of pediatric patients who were hospitalized between March 2020 and June 2021 in a tertiary pediatric hospital. A total of 1,103 consecutive pediatric patients tested positive for COVID-19, and 232 were admitted. All patients underwent cardiac evaluation with electrocardiogram, echocardiogram, and cardiac markers. Of these patients, 88 were diagnosed with myocardial injury but 1 patient refused to participate, therefore 87 patients were included in the study. Results: The median age at the time of diagnosis was 2 years (0-18), 38% had pre-existing comorbidities, and the mortality was 12% (n = 11). Cardiac evaluation has revealed high levels of troponin I in 63%, and electrocardiogram and echocardiogram abnormalities in 81% and 22% respectively. We found that high levels of inflammatory markers had higher mortality, but they didn’t emerge as significant predictors of mortality when adjusted for other variables. Patients without pre-existing comorbidities were less likely to die in both univariate and multivariate analysis. Conclusions: Our findings may help healthcare providers better understand the cardiac implications of COVID-19 and define the necessity of cardiac surveillance amongst hospitalized pediatric patients.